Self‐defined residential neighbourhoods: size variations and correlates across five European urban regions. (January 2016) - Charreire, H.; Feuillet, T.; Roda, C.; Mackenbach, J. D.; Compernolle, S.; Glonti, K.; Bárdos, H.; Le Vaillant, M.; Rutter, H.; McKee, M.; De Bourdeaudhuij, I.; Brug, J.; et al.
Summary: The neighbourhood is recognized as an important unit of analysis in research on the relation between obesogenic environments and development of obesity. One important challenge is to define the limits of the residential neighbourhood, as perceived by study participants themselves, in order to improve our understanding of the interaction between contextual features and patterns of obesity. An innovative tool was developed in the framework of the SPOTLIGHT project to identify the boundaries of neighbourhoods as defined by participants in five European urban regions. The aims of this study were (i) to describe self‐defined neighbourhood (size and overlap with predefined residential area) according to the characteristics of the sampling administrative neighbourhoods (residential density and socioeconomic status) within the five study regions and (ii) to determine which individual or/and environmental factors are associated with variations in size of self‐defined neighbourhoods. Self‐defined neighbourhood size varies according to both individual factors (age, educational level, length of residence and attachment to neighbourhood) and contextual factors. These findings have consequences for how residential neighbourhoods are defined and operationalized and can inform how self‐defined neighbourhoods may be used in research on associations between contextual characteristics and health outcomes such as obesity.